Genetic Risk Score Predicts Late-Life Cognitive Impairment. (23rd August 2015) - Wollam, Mariegold E.; Weinstein, Andrea M.; Saxton, Judith A.; Morrow, Lisa; Snitz, Beth; Fowler, Nicole R.; Suever Erickson, Barbara L.; Roecklein, Kathryn A.; Erickson, Kirk I.
Abstract : Introduction . A family history of Alzheimer's disease is a significant risk factor for its onset, but the genetic risk associated with possessing multiple risk alleles is still poorly understood. Methods . In a sample of 95 older adults (Mean age = 75.1, 64.2% female), we constructed a genetic risk score based on the accumulation of risk alleles in BDNF, COMT, and APOE . A neuropsychological evaluation and consensus determined cognitive status (44 nonimpaired, 51 impaired). Logistic regression was performed to determine whether the genetic risk score predicted cognitive impairment above and beyond that associated with each gene. Results . An increased genetic risk score was associated with a nearly 4-fold increased risk of cognitive impairment (OR = 3.824, P = .013) when including the individual gene polymorphisms as covariates in the model. Discussion . A risk score combining multiple genetic influences may be more useful in predicting late-life cognitive impairment than individual polymorphisms.